Feasibility of a Drone-Based Road Network Inspection System - Dávid Szilágyi; Dávid Sziroczák; Dániel Rohács; Ármin Fendrik (Engineering Proceedings)
Data collection using drones is a widely used practice today. This capability can be used to develop a drone-based road surface inspection system aimed at increasing user (driver) safety and providing information to the owners and maintainers to assess the status of their infrastructure assets. This paper presents an overview of the Turkish–Hungarian U-SOAR project, aimed at the prototype level development of such system. While the system is technically feasible, two key aspects were identified that requires focused further evaluation and development: the business model definition and the management of conflicts in operation. The paper highlights the key findings in these two areas. First, the methodology used to assess the possible business approaches is demonstrated, showing that in the context of these two countries, service provision providing processed data has the highest potential. Second, the requirements towards conflict management as a key part of safe operations are presented. This paper shows the proposed automated conflict management solution and the initial development and testing of the system.